2018
DOI: 10.1521/jscp.2018.37.5.325
|View full text |Cite
|
Sign up to set email alerts
|

School-Aged Children's Cognitive Interdependence as a Prospective Link Between Their Depressive Symptoms and Physiological Stress Reactivity

Abstract: Associations between children's depressive symptoms and physiological stress reactivity have been identified across many investigations. Similarly, a large body of literature explores the cognitive correlates of depressive symptomatology in childhood. To date, few studies conducted with children have integrated these approaches. In the present study, we examine a well-documented correlate of depression in adults; low cognitive interdependence (as measured via pronoun use, or we-ratio), in a child population. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Similarly, as confirmed by preliminary findings, discrepancies between physiological activation and reported reactivity to stressors are significantly associated with adverse health outcomes in school-age children and adolescents. 81…”
Section: Bridging Attachment Organization and Pain Experiences Using mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, as confirmed by preliminary findings, discrepancies between physiological activation and reported reactivity to stressors are significantly associated with adverse health outcomes in school-age children and adolescents. 81…”
Section: Bridging Attachment Organization and Pain Experiences Using mentioning
confidence: 99%
“…Similarly, as confirmed by preliminary findings, discrepancies between physiological activation and reported reactivity to stressors are significantly associated with adverse health outcomes in school-age children and adolescents. 81 Moreover, Kozlowska and Williams 45 found that 86% of children and adolescents with conversion and somatoform disorders, including functional pain syndromes, exhibit pattern of information processing related to inhibitory and/or excitatory self-protective strategies. Both anxious attachment developmental pathways (Types A and C) seem to contribute to adolescent and young adult conversion pathophysiology.…”
Section: Attachment and Pain In School Age And Adolescencementioning
confidence: 99%